Extrinsic cues, perceived quality, and purchase intention for private labels: Evidence from the Chinese market. Issue 3 (10th June 2019) - Yan, Liu; Xiaojun, Fan; Li, Jie; Dong, Xuebing
Abstract : Purpose: Based on the cue utilization theory and congruity theory, the purpose of this paper is to investigate the mediating effects of perceived quality on the relationships between category characteristics and purchase intention for private labels. Design/methodology/approach: To examine the research hypotheses, the authors conducted a questionnaire survey on 703 adult consumers in China. Findings: The results show that perceived quality fully mediates the relationships between category complexity, risk importance, category quality variation, product signatureness and purchase intention. In addition, consumers' knowledge moderates the relationship between perceived quality and purchase intention. The implications and future research directions are discussed in this study. Originality/value: The results show that the category complexity is positively related to consumers' perceived quality. Although opposite to the conclusions in prior research, the findings are consistent with the unique phenomenon in China, that is, to label the name and location of the contract manufacturers. The authors investigate the moderating role of consumer knowledge, which will provide meaningful guidance for the Chinese retailing market.